واقع ومتطلبات تطوير العائد الاقتصادي للتعليم الفني الصناعي في مصر - أحمد، سمير عبدالحميد القطب; زايد، أميرة عبدالسلام عبدالمجيد; محمود، مصطفى علي السيد (جامعة كفر الشيخ - كلية التربية, 2023)
هدفت الدراسة إلى الكشف عن واقع ومتطلبات تطوير العائد الاقتصادي للتعليم الفني الصناعي، وصياغة آليات لتنفيذ المتطلبات، واعتمد الباحث على المنهج الوصفي الإحصائي كمنهج للدراسة، وتوصلت الدراسة إلى أن هناك فجوة بين معدلات انفاق الدولة لتطوير منظومة التعليم الفني الصناعي وبين كفائتها الداخلية والخارجية فهناك قصور بها يزيد من الهدر للإنفاق على التعليم، كما أن هناك ضعف العائد الاقتصادي للتعليم الفني الصناعي يأتي على رأس الأولويات التي ينبغي العمل على الحد منها، وأن أهم متطلبات تطوير العائد الاقتصادي تقوم على تحسين الكفاءة الداخلية والخارجية وإنشاء الحاضنات التكنولوجية وتفعيلها داخل مدارس التعليم الفني، وقد أوصت الدراسة بتطوير رؤية مدارس التعليم الفني الصناعي بحيث تكون ملائمة لسوق العمل، وتوفير التمويل اللازم لإنشاء وتشغيل الحاضنات، والاستعانة ببعض الجهات الحكومية والخاصة، وتوفير ورش عمل وبرامج تدريبية للطلاب في مجالات العمل اليدوي، وتوفير الأدوات والتقنيات اللازمة لذلك. The study aimed to reveal the reality and requirements for developing the economic return of industrial technical education, and to formulate mechanisms to implement the requirements. The researcher relied on the descriptive statistical approach as a method for the study, The study concluded that there is a gap between the state’s spending rates to develop the industrial technical education system and its internal and external efficiency. There are deficiencies in it that increase the waste of spending on education. There is also a weak economic return for industrial technical education that is at the top of the priorities that should be worked to reduce. The most important requirements for developing economic returns are based on improving internal and external efficiency and establishing and activating technological incubators within technical education schools, The study recommended developing the vision of industrial technical education schools so that they are appropriate for the labor market, providing the necessary funding to establish and operate incubators, seeking assistance from some government and private agencies, providing workshops and training programs for students in the fields of manual work, and providing the necessary tools and techniques for that.
Keywords: التعليم الفني الصناعي -- التخطيط التربوي -- التنمية الاقتصادية -- البرامج التدريبية -- مصر